Modern views on intoxication in dental clinic and somatic pathology and features of development of an endotoxidrome at physical activities (Эндодонтия Today)
In this literature review presents data about etiological role of systemic endotoxemia and endotoksikoz in the development of dental and physical illness and physical activity as a factor contributing to the development of infectious disease in athletes.